Analisis Sektor Unggulan Di Kabupaten Sleman dan Kabupaten Gunungkidul - Karima Sharazati; Wiwin Priana Primandhana; Mohammad Wahed (Ridwan Institute, 2021)
Development of an increasingly complex area in the era of regional autonomy resulting in interstate competition becomes tighter. For the welfare of the community to remain stable and even incresing, local governments must improve the competitiveness of their territory. This study aims to identify economic sectors that will be the priority of regional development based on regional influence, regional specialization, and competitive advantage of economic sector in DIY Province. This study uses to determine the leading sectors in the regional economy of Sleman Regency and Gunungkidul Regency. The data collection techniques used in this study were BPS data and related literature. The sample in this study used 17 economic sectors in GRDP (Gross Regional Domestic Product) of Sleman Regency and Gunungkidul Regency. Technical data analysis in this study using Shift Share analysis, Location Quotient, and Klassen’s Typology. Based on the three analysis, it was found that the Accommodation and Food and Drink sectors were the leading sectors in Sleman Regency. And the Other Services sector is the leading sector of Gunungkidul Regency.